Development of biodegradable plastic composite blends based on sago derived starch and natural rubber - Yiu, Pang Hung; Balasubramaniam, Jaya Raj; Kiing, Sie Cheong; Lee, H. H.; Wong, Sie Chuong; Amarthalingam, Rajan (2009)
Polyethylene is a widely used packaging material, but its non-biodegradable nature lead to waste disposal problems. This has caused concerns and increased efforts on research and development of biodegradable plastics from natural resources as alternatives to the petroleum-derived plastics. In this study, biodegradable plastic composites were prepared by blending thermoplastic starch with natural rubber in the presence of glycerol as plasticizer. Local sago starch was casted with 0.5 to 10% of natural rubber to prepare the bioplastic. The products were characterized by differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), water absorption test, biodegradability test, hydrolysis test and mechanical analysis. Composites with increasing natural rubber latex component from 0.5 to 10% showed melting temperature in the range of 120 to 150 °C. The water absorption characteristic, biodegradability and tensile strength decreased by 11.21%, 30.18% and 20.733 MPa respectively. However, the elongation at break was increased from 26.67 to 503.3%. This study showed that sago starch has good potential in bioplastic production with good miscibility and compatibility.